HISTORICAL WORKS OF ABULGOZI BAHADIRKHAN LANGUAGE AND STYLE - Mustofoyeva Muyassar (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article analyzes the language and style of Abulghazi Bahadir Khan’s historical works, as well as the additions and words used in the literary language of that time.